DEVELOPMENT OF A TRAINING PACKAGE FOR YOUNG TOURIST GUIDES: A CASE STUDY OF KOH YO SUB-DISTRICT, MUANG DISTRICT, SONGKHLA PROVINCE. - CHIRANDON, AMONRAT (JOURNAL OF HUMANITIES AND SOCIAL SCIENCES SONGKHLA RAJABHAT UNIVERSITY, 2020)
The purposes of this research were to 1) study the basic requirements for developing the training package of English communication for young tourist guides in Koh Yo Sub-District, Muang district, Songkhla province and 2) design and evaluate efficiency of the developed training package. The research instruments were 1) questionnaire was used to collect data from local people and analyze data were frequency, percentage, average,standard deviation 2) structure interview was used to collect data from stakeholders and involved informants and content analysis and 3) training package’s quality assessment form was used to collect data from academician’s informants and analyze data were average and standard deviation. The results showed that 1) The basic requirements for developing the training package found that opinion’s level of local people as a whole high level, opinion of stakeholder and involved informants consisted of content, qualifications of tour guides and learning activities, and contextual content synthesis of training package found that the training package consisted of rationale, objective, content, training methods, training activities, media and learning resources, measurement and evaluation, and seven lesson plans. 2) Develop and evaluate efficiency of the training package found that suitability’s level of the training package as a whole highest level.